New Pages of the [un]known story - Walczak-Mikołajczakowa, Mariola (Poznańskie Studia Slawistyczne, 2019)
The article discusses the book by Diana Ivanova История на новобългарския книжовен език – a new textbook on the history of literary Bulgarian language. Starting from a discussion of terminology related to concepts the Old Bulgarian and New Bulgarian language, first presents the history of the scientific discipline as the history of the New Bulgarian literary language (NBKE), and then the textbooks used so far in the university didactics. It is necessary to indicate a new content of the discussed monograph, in which a significant novum is the different perception of the beginnings of NBKE and chapters on the activities of the literary society from Brasov and biblical translations into a language understandable to the reader in the 19th century.